Using Herringbone Technique in Teaching Reading Narrative Text at the Eighth Grade Students of SMP Negeri 9 Parepare - Sudarmanto Sudarmanto (EDUVELOP, 2018)
This research discussed how the use herringbone technique to improve the students’ ability in reading. This research used quasi experimental design that applied a pre-test and post-test design. The data was analyzed by using t-test. The population of this research was the eight year students of SMP Negeri 9 Parepare in academic year 2013/2014. There were two classes, a class for experimental class and a class for control class. It utilized cluster random sampling technique. The number of each class was 30 students. The instrument used in this research was reading test use of herringbone technique in learning reading. The result of this research was a significant difference between experimental group and control group. This indicates the mean score of the post-test of experimental group was 97 while that of the control group was 92. Moreover, the t-test value (7,24) was higher than t-table value (2.021). In other words, Hypothesis Alternative (H1) was accepted and Hypothesis Null (H0) was rejected. This means that Using Herringbone technique can improve the students’ reading comprehension by using herringbone technique.